Are the fishers of Sorsogon knowlegeable about and willing to farm seaweed Ulva? - Dumilag, Richard V. (Philippine Journal of Science, 2023)
The province of Sorsogon in the Philippines has a strong history of introducing farmed seaweeds and subsequently assembling farmers who put together the required enthusiasm to ensure successful production. Ulva is a green seaweed that has a wide range of commercial uses. Its farming, therefore, presents a promising opportunity for fishers to diversify their income streams and reduce their reliance on fishing. Using survey-based responses collected from fishers in Bulusan, Sorsogon, this study aimed to assess the knowledge of the local Ulva resources and the willingness of fishers to engage in Ulva farming, including identifying the challenges that may hinder its adoption. Our findings revealed that most Bulusanon fishers were knowledgeable about Ulva resources and could identify barriers to farming. They were generally receptive to engaging in farming Ulva, primarily due to the perceived economic benefits. Fishers with considerable knowledge about Ulva distribution were more likely to farm. While most Bulusanon fishers desired to farm Ulva, they were unlikely to be willing to learn, invest, or spend time doing it. Fishers may lack the desire to farm because, in part, it requires different skill sets as well as the challenges associated with marketing. This study provides valuable insights into the development of targeted interventions to promote the adoption of Ulva farming in the region.